Multifactor leadership questionnaire (rater form 5x-short form) - Moey, Soo Foon (2018)
A preliminary pre-test questionnaire was developed based on the review of related literature on the theoretical constructs and the underlying factors. The preliminary pre-test questionnaire was tested on a sample of 30 respondents. Items that did not perform statistically were either refined or removed to improve the measurement scale before being administered to the targeted sample in the pilot study. The pre-test questionnaire consisted of 43 items with four demographic items to measure the four constructs as discussed in the literature review: (i) Transformational Leadership Style, (ii) Transactional Leadership Style, (iii) Nurse Educator Demographic Factors and (iv) Overall Job Satisfaction (Table 1). The number of items measuring the construct range from four to 20. In ensuring greater validity and reliability of measurements, DeVellis (1991) has suggested the use of interval scales to measure variables that were not directly observed. Thus, interval scale with 1, being “Strongly Disagree” to 10, being “Strongly Agree” was utilized to record the responses for leadership styles in the study. Multifactor Leadership Questionnaire